Count the ways eaudiobook A novel. - Maynard, Joyce (2021)
In her most ambitious novel to date, New York Times bestselling author Joyce Maynard returns to the themes that are the hallmarks of her most acclaimed work in a mesmerizing story of a family—from the hopeful early days of young marriage to parenthood, divorce, and the costly aftermath that ripples through all their lives Eleanor and Cam meet at a crafts fair in Vermont in the early 1970s. She's an artist and writer, he makes wooden bowls. Within four years they are parents to three children, two daughters and a red-headed son who fills his pockets with rocks, plays the violin and talks to God. To Eleanor, their New Hampshire farm provides everything she always wanted—summer nights watching Cam's softball games, snow days by the fire and the annual tradition of making paper boats and cork people to launch in the brook every spring. If Eleanor and Cam don't make love as often as they used to, they have something that matters more. Their family. Then comes a terrible accident, caused by Cam's negligence. Unable to forgive him, Eleanor is consumed by bitterness, losing herself in her life as a mother, while Cam finds solace with a new young partner. Over the decades that follow, the five members of this fractured family make surprising discoveries and decisions that occasionally bring them together, and often tear them apart. Tracing the course of their lives—through the gender transition of one child and another's choice to completely break with her mother—Joyce Maynard captures a family forced to confront essential, painful truths of its past, and find redemption in its darkest hours. A story of holding on and learning to let go, Count the Ways is an achingly beautiful, poignant, and deeply compassionate novel of home, parenthood, love, and forgiveness.